Estrategias de enseñanza y resolución de problemas matemáticos según la percepción de estudiantes del cuarto grado de primaria de una institución educativa - Ventanilla - Gutiérrez Cherres, José Antonio (2012)
This research is descriptive correlational. Aimed to determine the correlation between teaching strategies and solving mathematical problems as perceived by the fourth grade students of an educational institution of Ventanilla. The sample used was not random about availability, comprised of 120 children ranging in age from 8 to 10 years. The instruments used were the Questionnaire on the perception of teaching strategies in the curriculum area of mathematics and the Test of solving mathematical problems (Ministry of Education, validated and adapted by Cherres, 2011). The results showed that there is a low positive relationship between teaching strategies in all its dimensions and the ability to solve mathematical problems, as perceived by the students of the fourth grade of primary education in a public school of Ventanilla.